Strategic Implementation of Social Media for Kampung Inggris Betang Itah: Enhancing Engagement and Reach - Nugraha, Richard Ferry; Amalia, Novika; Marcelino, Riandi; Olivia, Tracy; Teresa, Yulia (Universitas Lambung Mangkurat, 2025)
This community service project aims to increase public awareness of the existence of Kampung Inggris Betang Itah in Palangka Raya, Central Kalimantan, as a means to support the English learning opportunity for the local community. By applying the ABCD approach, this project aims to develop the potential in the Kampung Inggris Betang Itah community, addressing challenges such as limited English tutor volunteers, a low number of students, and low exposure to the community. The first activity of the project was carried out by applying a 30-day content plan through Instagram, while the second gave training to the public relations team of Kampung Inggris Betang Itah regarding copywriting and social media management. The results show a significant increase in content engagement and reach, such as likes, comments, messages, and the number of audiences seeing the content. It also includes the number of Instagram followers, new students, and English tutor volunteers. Moreover, the public relations team of Kampung Inggris Betang Itah also had a good perception of the copywriting and social media management training.